Unveiling high-Tc superconductivity: probing CuO2 planes in infinite-layer cuprates - Rui-Feng Wang; Can-Li Song; Xu-Cun Ma; Qi-Kun Xue (AAPPS Bulletin)
Abstract The quest to unravel the intricacies of high-Tc superconductivity and strongly correlated electrons in cuprates has spurred a novel focus on direct probing of the CuO2 planes through scanning tunneling microscopy. Infinite-layer (IL) cuprates, featuring a CuO2-terminated surface, emerge as optimal systems for this investigation. Leveraging controllable growth via molecular beam epitaxy, both electron- and hole-doped IL cuprates are realized, with surface structure and c-axis length serving as distinctive markers. A consistent pattern in the Mott transition is established, revealing that doping merely shifts the Fermi level without inducing changes in the Mott band structure, thereby suggesting a self-modulation doping scenario. Furthermore, the identification of a nodeless superconducting gap in the CuO2 planes challenges conventional notions derived from charge reservoir layers, advocating for a quantum well interpretation of cuprate superconductivity. This review sheds light on the distinct roles played by CuO2 layers and charge reservoir layers, promising a more profound comprehension of cuprate superconductivity through the lens of the CuO2 surface.